2018
DOI: 10.4067/s0717-75262018000300245
|View full text |Cite
|
Sign up to set email alerts
|

Rinoseptoplastía: Experiencia de 3 años en la Pontificia Universidad Católica de Chile

Abstract: La rinoseptoplastía es una cirugía compleja y desafiante. Permite resolver problemas estéticos y funcionales de la nariz. Objetivo: Describir la experiencia en rinoseptoplastías realizadas en el Comité de Nariz en nuestro centro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…However, a UK study reported that only 73.3% of senior residents consider themselves prepared to perform a septoplasty independently 3 . According to a study performed in our institution, residents were exposed to a mean of 18 endonasal septoplasties during their training in otolaryngology 6 . Other Chilean institutions report a median of only 12 septoplasties per trainee 7 .…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…However, a UK study reported that only 73.3% of senior residents consider themselves prepared to perform a septoplasty independently 3 . According to a study performed in our institution, residents were exposed to a mean of 18 endonasal septoplasties during their training in otolaryngology 6 . Other Chilean institutions report a median of only 12 septoplasties per trainee 7 .…”
mentioning
confidence: 88%
“…3 According to a study performed in our institution, residents were exposed to a mean of 18 endonasal septoplasties during their training in otolaryngology. 6 Other Chilean institutions report a median of only 12 septoplasties per trainee. 7 This situation has significantly worsened during the past year due to the coronavirus disease 2019 (COVID- 19) pandemic, which has led to a restriction in elective procedures, reducing residents' exposure to this procedure.…”
mentioning
confidence: 99%
“…La rinoplastia, permite abordar los problemas no solo estéticos sino también funcionales nasales, ya que no se pueden separar uno de otro, comparando con estudios de la región, como el llevado a cabo en la Pontifica Universidad Católica de Chile, de mayor flujo de pacientes que nuestro servicio, en un periodo similar de tiempo llevaron a cabo 265 rinoplastias, al igual que en nuestro estudio la mayoría de sus pacientes fue del sexo femenino (8).…”
Section: Discusionunclassified